2015
DOI: 10.1097/iae.0000000000000849
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of Foveal Avascular Zone in Diabetic Eyes Evaluated by en Face Optical Coherence Tomography Angiography

Abstract: Our data suggest that diabetic eyes show retinal microcirculation impairment in the macula even before retinopathy develops. En face OCTA is a useful noninvasive screening tool for detecting early microcirculatory disturbance in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
298
4
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(350 citation statements)
references
References 27 publications
28
298
4
10
Order By: Relevance
“…Currently, OCTA enables a regular FAZ assessment in diabetic patients. Further studies are necessary to evaluate the utility of this parameter in assessment of diabetic retinopathy progression [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, OCTA enables a regular FAZ assessment in diabetic patients. Further studies are necessary to evaluate the utility of this parameter in assessment of diabetic retinopathy progression [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…SS-OC-TA may be able to overcome signal attenuation, such as from the RPE, media opacities, and any overlying hemorrhage. Takase et al, [6] detected the area of the foveal avascular zone (FAZ) by enface OCTA (AngioVue, Avanti OCT; Optovue), and then evaluated the diferences between healthy and diabetic eyes. They found that the FAZ area in the deep plexus layer was significantly larger in diabetic eyes than in healthy eyes.…”
Section: Applications Of Octamentioning
confidence: 99%
“…Our center reviewed literature regarding the OCTA applications in diabetics which is going to be published soon. Available reports are few, but interesting facts regarding the FAZ is published [7][8][9][10][11][12][13][14][15][16][17][18]. The FAZ in normal individual was described in the OCTA as an intact well-demarcated round or oval area of reduced capillary density with a border without gaps, holes or interruption of the capillary network in both superficial and deep plexuses.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may also add to our knowledge regarding pathophysiology behind the ischemic changes in DR. The OCTA has increased feasibility of qualitative FAZ assessment; but the most impressing are regarding the quantitative FAZ assessments the FAZ size increased significantly by progression of retinopathy grade in almost all reports [9][10][11][12][13][14][15][16][17]. (Table 1) has summarized current available range of the mean FAZ size values in different grades of disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation